Workshop Pembuatan Modul Digital Berbasis Canva Untuk Guru di SDN 4 Balangnipa - Jusman Jusman (Prodi PGSD Unsultra, 2025)
Technological advances have brought significant changes in the world of education, including in the development of digital teaching materials. Elementary school teachers are required to be able to present interesting and interactive learning materials in order to increase student involvement in the learning process. However, many teachers still have difficulty in designing effective and interesting digital modules. Therefore, this community service activity aims to improve teacher skills in creating Canva-based digital modules. The workshop implementation method consists of training, direct practice, and evaluation of participants' work. The results of the activity showed that teachers experienced an increase in their understanding and skills in designing more interesting and interactive digital modules. Thus, this workshop makes a real contribution to improving the quality of learning in Elementary Schools.